PENDUGAAN TINGKAT KONTAMINASI LOGAM BERAT PB, CD DAN CR PADA AIR DAN SEDIMEN DI PERAIRAN SEGARA ANAKAN, CILACAP - Nuning Vita Hidayati; Asrul Sahri Siregar; Lilik Kartika Sari; Gayuh Laksana Putra (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2014)
A study was carried out to investigate the concentrations and contamination levels of heavy metals in the sediments of Segara Anakan, Cilacap for three heavy metals (Cd, Pb, and Cr). sediments samples were collected from six sites during February 2013. The samples were analyzed to determine their heavy metals, pH and total organic carbon (TOC) content. Environmental assessment of sediments pollution by heavy metal was carried out using Contamination Factor (CF), Enrichment Factor (EF) by comparing to CCME, ANZECC and NOAA targets for sediment quality Guidelines. The results of this simple comparison revealed that, the Segara Anakan sediment concentrations of heavy metals are within the permissible limits of standards for Pb. CF value of Pb, Cd, and Cr (0.86, 10.8, dan 3.3) indicated no contamination for Pb (0.86), very strong contamination for Cd (10.8), and moderately to strong contamination for Cr. Calculated EF of the Pb, Cd, Cr in sediment were 1.50, 18.8, dan 5.7 indicating deficiency to low enrichment for Pb anrophogenically, and significant enrichment for Cd and Cr. According to the CF and EF value, Segara Anakan may face a severe heavy metal pollution contamination problem in the future.Keywords: sediments, contamination, anthropogenic